A theory of strategic vertical DFI and the missing pollution-haven effect - Zhihao Yu (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper develops a theory of strategic vertical DFI (direct foreign investment) to suggest an explanation for the empirical puzzle of the missing `pollution-haven' effect. It focuses on a firm's strategic incentive to create multi-market interdependence (in addition to other conventional incentives for DFI) and suggests that the empirical investigations on pollution-haven effects based on environmental compliance costs might be complicated by such strategic behaviour. The theory provides particular implications for the empirical research in this area and some broader implications for the theory of DFI.
Keywords: F18; 330; Trade and environment; pollution-haven hypothesis; vertical DFI/FDI; Direktinvestition; Umweltpolitik; Standortfaktor; Vorprodukt; Wettbewerb; Marktstruktur; Theorie